Analisis Efektivitas Pemasangan TREPOS Pada Unit Excavator Kelas 20 Ton Sebagai Upaya Preventive Maintenance Komponen Undercarriage - Alva Rizki Amanullah; Harjono; Irfan Bahiuddin; Sugiyanto; Muhamad Sandi Isyanto; Arif Khaerudin; Imam Muslih (Jurnal Teknologi dan Rekayasa Alat Berat, 2026)
The operational pattern of excavator units, particularly travel duration and frequency, is one of the dominant factors contributing to the increased occurrence of undercarriage component breakdowns. Therefore, a system-based operational control mechanism is required to limit excessive travel operations that do not comply with manufacturer standards. This study aims to analyze the effectiveness of installing an additional controller in the form of a Travel Protection System (TREPOS) in a case study of a 20-ton class excavator as a preventive maintenance strategy to improve the reliability of undercarriage components. The research employs an integrated analytical approach comprising Failure Mode and Effect Analysis (FMEA), PDCA, and PICA, along with a comparative analysis of operational data before and after TREPOS implementation. The results indicate that excessive travel duration and intensity are among the dominant factors causing unscheduled breakdowns in the undercarriage system. The implementation of TREPOS effectively controls the unit’s operational pattern by reducing continuous travel time exceeding 20 minutes and suppressing the occurrence of unscheduled breakdowns during the study period. Furthermore, TREPOS implementation has the potential to extend the service life of undercarriage components by up to 48% for carrier rollers, 42% for track rollers, 33% for sprockets, and 86% for track links, which overall contributes to a reduction in maintenance costs.